Analysis of the additional cost of addressing per- and polyfluoroalkyl substance contamination from landfill leachate by reverse osmosis membranes in Thailand. (February 2022) - Kanchanapiya, Premrudee; Tantisattayakul, Thanapol
Abstract: Per- and polyfluoroalkyl substances (PFAS), persistent organic pollutants, have been found in landfill leachate (LL) and can lead to environmental contamination. Recently, more stringent global regulations to control the maximum levels of PFAS have forced landfill authorities to improve treatment technologies to meet higher effluent quality standards. This study analyzed the additional cost of the treatment process to remediate PFAS contamination from LL in Thailand using a two-pass reverse osmosis (RO) system, including pretreatment and the use of evaporation ponds. The total estimated LL volume from 111 sites of sanitary landfills was ascertained using the water balance method, and then the overall project cost in the form of the net present cost (NPC) was evaluated. The capital investment, expense, and related operating and maintenance costs over the project lifetime were taken into account. The results showed that the total estimated LL volume was 17.5 m 3 /yr. To handle this amount of LL, the NPCs of the RO system were found to be 577.9 mil. USD for the system with an evaporation pond and 391.9 mil. USD for the system without an evaporation pond. The treatment unit costs ranged from 1.72–2.71 USD/m 3 for the system with an evaporation pond and ranged from 1.06 to 2.09 USD/m 3 for the system without an evaporation pond, depending on the size of the landfills. Based on these results, technological, operational, financial, and regulatory policy recommendations are presented. Graphical abstract: Unlabelled Image Highlights: Implementation cost of RO to remediate PFAS from landfill leachate was analyzed. The net present costs of the RO system were found to be 391–5789 mil.USD. The treatment unit costs ranged from 1.72 to 2.71 USD/m 3 . Policy recommendations are presented.